2001
DOI: 10.1207/s15327949pac0703b_5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of Korean reunification: Explicit and implicit national attitudes and identity of South Koreans and North Korean defectors.

Abstract: Two studies investigated the explicit and implicit attitudes toward, and identification with, South and North Korea by a sample of South Koreans and North Koreans who voluntarily defected to the South. North Korean defectors showed (a) more positive evaluations of South Korea on explicit self-report measures, but more favorable evaluations of the North on an implicit measure, and (b) on average, North-South neutral identity on an explicit measure, but stronger self-association with the North on an implicit mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…To our knowledge, only two studies have employed implicit methods to measure processes related to acculturation. The first of these studies explored implicit cultural identification with South and North Korea in a sample of North Koreans who had defected to South Korea (Kim & Oh, ). The new citizens of South Korea (i.e., refugees from North Korea) responded to explicit and implicit measures of North–South Korean identity.…”
Section: Assessment and Definitions Of Acculturationmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only two studies have employed implicit methods to measure processes related to acculturation. The first of these studies explored implicit cultural identification with South and North Korea in a sample of North Koreans who had defected to South Korea (Kim & Oh, ). The new citizens of South Korea (i.e., refugees from North Korea) responded to explicit and implicit measures of North–South Korean identity.…”
Section: Assessment and Definitions Of Acculturationmentioning
confidence: 99%
“…The first study aimed to extend the preliminary work of Kim and colleagues (Kim et al, ; Kim & Oh, ) by establishing the GNAT as a sound measure of implicit cultural identification, which can assess implicit identification in a manner that is suitable for application to Berry's acculturation attitudes framework. The GNAT is a speeded categorization task that measures the accuracy of implicit associations between target categories.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This study not only contributes to providing a broadened understanding of a new generation of NKDs, but it also offers ways to overcome prevailing negative perspectives about NKDs in the South. We should remember that NKMs are not only the emerging population group in South Korean society, but they are also a promising generation with the possibility to play a leading role in achieving future reunification (D. Kim & Oh, 2001; A.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…
Kim and Oh (2001) reported the existence of implicit (nonconscious) prejudicial attitudes toward South and North Korea by South Koreans and by North Koreans who voluntarily defected to South Korea, although the two groups showed no difference in explicit (conscious) forms of prejudice. This study followed up on the explicit and implicit attitudes of South Koreans initially reported in 1998, by assessing the attitudes shortly after the North and South Korea Summit held in June 2000, as well as 2 years later (2002).
…”
mentioning
confidence: 95%